Frequency of Breast Cancer Surgery Related Arm Lymphedema at King Abdulaziz University Hospital 2008 – 2015, a Tertiary Center Experience, Jeddah, Saudi Arabia - Sabah S. Moshref,; Yasir S. Jamal,; Zuhoor K. Al Gaithy,; Shadi S. Alkhayyat,; Basim A. Awan,; Mahmoud Fakiha,; Hossam Ammar,; Abdullah Bamashmos,; Mawaddah Alrajraji,; Mohammad Abolhamayl, (Journal of King Abdulaziz University: Medical Sciences, 2023)
The purpose of this retrospective study was to investigate the frequency of breast cancer-related lymphedema at King Abdulaziz University Hospital and factors associated with it. Eighty-four breast cancer-related lymphedema patients were recruited from Plastic and Reconstruction Surgery Unit, King Abdulaziz University Hospital, Jeddah, Saudi Arabia after breast cancer treatment during the period from 2008 till 2015. According to the circumference difference between healthy and affected arm, lymphedema degree was categorized into mild (> 5-10%), moderate (> 10-15%) and severe (> 15%). From a total of 598 patients who underwent breast cancer resection, 84 (14.05%) patients developed breast cancer-related lymphedema. In out of the 84 patients who developed arm lymphedema, the treatment was mostly modified radical mastectomy and radiotherapy (n = 59, 70.24%); followed by lumpectomy plus axillary lymph node dissection and radiotherapy (n = 18, 21.43%), simple mastectomy (n = 5, 5.95%) and lumpectomy with sentinel lymph node dissection and radiotherapy (n = 2, 2.38%) with statistical significant difference between them (P = 0.0001). The frequency of lymphedema in our institution is 14.05%. It is mostly moderate, appears during the 1st year after surgery in patients who underwent modified radical mastectomy and radiotherapy, aged more than 60 years and obese.